Light quantum control of persisting Higgs modes in iron-based superconductors - C. Vaswani (Nature Portfolio, 2021)
A collective excitation called Higgs mode may arise in multi-band superconductors via strong interband interaction, but it is yet to be accessed. Here, the authors observe a tunable coherent amplitude oscillation of the order parameter in Ba(Fe1−x Co x )2As2, suggesting appearance and control of the Higgs mode by light tuning interband interaction.